Craniocervical myology and functional morphology of the small-headed therizinosaurian theropods Falcarius utahensis and Nothronychus mckinleyi. - David K Smith (PLoS ONE)
Therizinosaurs represent a highly unusual clade of herbivorous theropods from the Cretaceous of North America and Asia. Following descriptions of the basicrania of the North American therizinosaurs Falcarius utahenisis and Nothronychus mckinleyi, the craniocervical musculature in both taxa is reconstructed using Tyrannosaurus, Allosaurus, and some extant birds as models. These muscles are subdivided into functional groups as dorsiflexors, lateroflexors, and ventroflexors. Lateroflexors and dorsiflexors in Nothronychus, but not Falcarius, are reduced, from the plesiomorphic theropod condition, but are still well developed. Attachments in both genera are favorable for an increase in ventroflexion in feeding, convergent with Allosaurus fragilis. Falcarius and Nothronychus are both characterized by a flat occipital condyle, followed by centra with shallow articular facets suggesting neck function very similar to that of an ostrich Struthio camelus. Neck movement was a combined result of minimal movement between the individual cervical vertebrae.